CURRENT RATIO, RETURN ON ASSET DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Imas Kismanah (Univesitas Muhammadiyah Tangerang, 2021)
The purpose of this study is to determine the effect of the current ratio, return on assets and leverage on financial distress partially and jointly in the Multi-Industry Sector companies listed on the Indonesia Stock Exchange (IDX). The research period used was 5 years, namely the period 2017 – 2020. The research population included all companies in various industrial sectors that were registered on the Indonesia Stock Exchange for the period 2017 – 2020. The sampling technique used was purposive sampling technique. Based on predetermined criteria obtained a sample of 17 companies. The type of data used is secondary data obtained from the Indonesian Stock Exchange website. The data analysis method used is panel data logistic regression analysis. The results of this study indicate that simultaneously the variables current ratio, return on assets and leverage affect financial distress. Arcially the variable current ratio and leverage have no effect on financial distress, while the variable return on assets has a significant negative effect on financial distress.Keywords: Financial Distress, Current Ratio, Return On Assets, Leverage